Studi Perbandingan Metode Penyimpanan Barang dalam Warehouse Management di Perusahaan Shipper - Fauzan, Nayla; Takaya, Rowlan (Universitas Pahlawan Tuanku Tambusai, 2025)
Warehouse is a place used to store goods, both for production and distribution purposes. Warehouse has several functions, including as a temporary storage location before the goods are distributed or used. Warehouse management plays an important role in the supply chain, helping to manage inventory and inventory control, therefore the warehouse has a very important role for a company. Warehouse also ensures that the flow of goods runs smoothly and on time. This study aims to analyze and compare which method of storing goods is the most effective and also efficient for Shipper company. This research method uses qualitative methods, methods that focus on information and data from Shipper Companies regarding the method of storing goods. Based on analysis using qualitative method, companies such as Shipper are more suitable for using pallete rack storage methods and dynamic racks. With this research, it is hoped that it can find out which storage method is more effective and also efficient for companies like Shipper.